The Multidomain Metaverse Cancer Care Digital Platform: Development and Usability Study - Sunghak Kim; Timothy Jung; Dae Kyung Sohn; Yoon Chae; Young Ae Kim; Seung Hyun Kang; Yujin Park; Yoon Jung Chang (JMIR Publications, 2023)
BackgroundAs cancer treatment methods have diversified and the importance of self-management, which lowers the dependence rate on direct hospital visits, has increased, effective cancer care education and management for health professionals and patients have become necessary. The metaverse is in the spotlight as a means of digital health that allows users to engage in cancer care education and management beyond physical constraints. However, it is difficult to find a multipurpose medical metaverse that can not only be used in the field but also complements current cancer care. ObjectiveThis study aimed to develop an integrated metaverse cancer care platform, Dr. Meta, and examine its usability. MethodsWe conducted a multicenter, cross-sectional survey between November and December 2021. A descriptive analysis was performed to examine users' experiences with Dr. Meta. In addition, a supplementary open-ended question was used to ask users for their suggestions and improvements regarding the platform. ResultsResponses from 70 Korean participants (male: n=19, 27% and female: n=51, 73%) were analyzed. More than half (n=37, 54%) of the participants were satisfied with Dr. Meta; they responded that it was an interesting and immersive platform (n=50, 72%). Less than half perceived no discomfort when using Dr. Meta (n=34, 49%) and no difficulty in wearing and operating the device (n=30, 43%). Furthermore, more than half (n=50, 72%) of the participants reported that Dr. Meta would help provide non-face-to-face and noncontact services. More than half also wanted to continue using this platform in the future (n=41, 59%) and recommended it to others (n=42, 60%). ConclusionsWe developed a multidomain metaverse cancer care platform that can support both health professionals and patients in non-face-to-face cancer care. The platform was uniquely disseminated and implemented in multiple regional hospitals and showed the potential to perform successful cancer care.